قياس فاعلية الواردات في التأثير على النمو الاقتصادي في سورية - اسماعيل, عصام (Latakia University Journal - Economic and Legal Sciences Series, 2018)
من المعروف أن النمو الاقتصادي هو الهدف الأساسي للسياسات الاقتصادية كافةً، ومن بين هذه السياسات السياسة التجارية والتي تعتبر من محددات النمو الاقتصادي، وفي هذا المجال تعتبر الواردات بتقسيماتها المختلفة إحدى وجهي هذه السياسة، والتي تلعب دوراً لناحية تأمين احتياجات الاقتصاد الوطني من السلع التي لايمكن توفيرها محلياً، وهذه الدراسة تناقش فعالية الواردات وذلك بحسب طبيعة استخدامها (واردات استهلاكية، وسيطة، رأسمالية) ودورها في التأثير على الناتج المحلي الإجمالي باعتباره الممثل للنمو الاقتصادي، حيث تبين أن العلاقة بين الواردات الرأسمالية والناتج كانت طردية وهو أمر منطقي، بينما كانت العلاقة عكسية مع كل من الواردات الوسيطة والاستهلاكية، وبشكل عام كانت العلاقة ضعيفة بين الواردات والناتج، وذلك على الرغم من أن تخفيف قيود الاستيراد وخاصةً على الواردات الرأسمالية كان لها أثر واضح على معدلات النمو الاقتصادي وخاصةً في النصف الأول من التسعينات، كما توصلت الدراسة إلى أن سياسة بدائل الواردات لم تستطع تغيير تركيبة الواردات لناحية تقليل نسبة الواردات الاستهلاكية. It is known that economic growth is the main objective of all economic policies. Among these policies are trade policy, which is one of the determinants of economic growth. In this regard, imports are considered one of the two aspects of this policy, which plays a role in securing the needs of the national economy. Locally, this study discusses the effectiveness of imports according to the nature of their use (consumer imports, intermediaries, capital) and their role in influencing GDP as the representative of economic growth. It was noted that the relationship between capital imports and GDP was positive, While the relationship was inverse with both intermediate and consumer imports, the overall relationship was weak between imports and output, although the relaxation of import restrictions, especially on capital imports, had a clear impact on economic growth rates, particularly in the first half of nineties, The study concluded that the import substitution policy was unable to change the composition of imports in terms of reducing the proportion of consumer imports.